2014
DOI: 10.1590/0103-166x2014000200004
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness indicators of bullying intervention programs: A systematic review of the international literature

Abstract: A systematic review was conducted in 2011, aiming to survey articles for indicators of effectiveness of intervention programs in bullying situations. A total of 165 articles were recovered, indexed in the databases: Web of Science, PsycInfo, Redalyc, Dialnet, and Eric. The analysis variables were: frequencies per journal, year, country, author, and effectiveness indicators of intervention programs in bullying situations. The "International Journal of Psychology" and "Psychological Therapy" had the highest perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
0
7
0
4
Order By: Relevance
“…In this perspective, the construction of a culture of non-violence is associated with a broad understanding of the phenomenon. Previ-ous studies have suggested that the level of perception, knowledge and beliefs about bullying among school-age youth, teachers and the school community significantly affect the prevalence rates of the phenomenon 3,8,18,19 . In the same direction, the dimensions that are most related to the central perspective, related to the manifestations of the phenomenon and exemplifications, reflect the real experience of the daily life, or are hypothesized as the best resource to explain how adolescents interpret bullying.…”
Section: The Person Feels Like Mutilating Herself; That Person Startsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this perspective, the construction of a culture of non-violence is associated with a broad understanding of the phenomenon. Previ-ous studies have suggested that the level of perception, knowledge and beliefs about bullying among school-age youth, teachers and the school community significantly affect the prevalence rates of the phenomenon 3,8,18,19 . In the same direction, the dimensions that are most related to the central perspective, related to the manifestations of the phenomenon and exemplifications, reflect the real experience of the daily life, or are hypothesized as the best resource to explain how adolescents interpret bullying.…”
Section: The Person Feels Like Mutilating Herself; That Person Startsmentioning
confidence: 99%
“…In this sense, prevention and intervention programs should consider the symbolic and conceptual value that bullying has in the view of students 3,18,19 . This level of approach requires the operationalization of qualitative studies that offer diverse options to identify variables that are significant for the phenomenon, such as motivations, causes, implicit situations such as social exclusion, prejudice and fear, as well as specific aspects of group relationships among students that are less visible in large-scale investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Estes estudos buscaram sinalizar a efetividade e qualidade dos programas de prevenção e enfrentamento da violência realizados em espaços escolares (FARRELL, 2001;GOTTFREDSON;GOTTFREDSON, 2002;MYTTON et al, 2002;HUMPHRIES;KEENAN, 2006;OZER, 2006;PARK-HIGGERSON et al, 2008;PAYNE, 2009;ECKERT, 2010;SALGADO et al, 2014;THOMPKINS et al, 2014).…”
Section: ) Estudos De Revisão Da Literatura Sobre a Qualidade E A Efunclassified
“…En referencia a publicaciones sobre programas de intervención y prevención de la violencia, España aparece como el país más productivo en la literatura internacional, (Salgado, Senra y Lourenco, 2014) aunque se aprecia una gran variabilidad de métodos y bases teóricas. Emprender investigaciones rigurosas de evaluación de los programas e instrumentos de formación de competencias socio-emocionales es un punto clave, a tener en cuenta, entre los objetivos de investigaciones futuras, ya que son muy pocos en España los programas que se evalúan de forma científica y apenas se recurre al uso de diseños experimentales y psicométricos fiables (Repetto y Pena, 2010).…”
Section: Horizontes En La Investigaciónunclassified